THE EFFECT OF ROSELLE EXTRACT AND EGGSHELL POWDER CONCENTRATION ON THE CHARACTERISTICS OF CHITOSAN BASED SMART EDIBLE FILM - Russel Jonathan; Erni Setijawaty; Adrianus Rulianto Utomo; Ignasius Radix AP Jati (SAGU, 2026)
Smart edible film packaging is produced from consumable materials and functions as an indicator of food quality. This study aims to evaluate the effects of incorporating roselle flower extract and chicken eggshell powder, as well as their interaction, on the physicochemical properties of chitosan-based smart edible films. A factorial Randomized Block Design (RBD) was applied, with roselle extract concentrations of 0 (control), 1:30 (w/v), and 1:15 (w/v). Eggshell powder was added at concentrations of 0 (control), 0.15% (w/v), and 0.30% (w/v). The evaluated parameters included total phenolic content, total anthocyanins, antioxidant activity, tensile strength, elongation at break, water vapor transmission rate (WVTR), and film color. Additionally, changes in the color, aroma, and pH of chicken meat samples were assessed on storage days 0, 1, 2, and 3. Data were analyzed using ANOVA (α = 5%), followed by Duncan’s Multiple Range Test (DMRT) (α = 5%). The resulting smart edible films exhibited total phenolic contents of 87.0711–1007.8933 mg GAE/100 g, total anthocyanins of 0.16–5.75 mg cy-3-glu equivalent/100 g, antioxidant activities of 5.5968–57.2047% RSA, WVTR values of 142.7795–240.9004 g/m²/24 h, tensile strengths of 1.511–10.030 N/mm², and elongation percentages of 0.64–21.11%. Significant interactions between treatments were observed for WVTR, tensile strength, and elongation at break. The developed smart edible film effectively functioned as a freshness indicator through detectable color changes during storage and helped reduce the extent of color, aroma, and pH alterations in steamed chicken meat.